Decisions of commercial banks under risk conditions and uncertainty - Rodríguez Nava, Abigail; Venegas Martínez, Francisco (Estudios Económicos de El Colegio de México, 2009)
This paper develops and optimization model that describes the decision process of a representative commercial bank in an uncertain environment. In the proposed model the magnitude of deposits and bank loans are driven by diffusion stochastic processes. Moreover, the model considers instant default probabilities associated with customers receiving credits. The model generates closed-form solutions for the prices of the bank services that maximize its benefit, and from such prices the financial markup and the risk markup are obtained. Finally, an application of the model for Mexican commercial banks through Monte Carlo simulation is carried out.